Appreciation of peer reviewers for 2016. Issue 6 (22nd June 2017) - Montanari, Alberto; Bahr, Jean; Blöschl, Günter; Cai, Ximing; Mackay, D. Scott; Michalak, Anna; Rajaram, Harihar; Sanchez‐Vila, Xavier
Abstract: On behalf of the journal, the American Geophysical Union, and the scientific community, the editors would like to sincerely thank those who reviewed manuscripts for Water Resources Research in 2016. Their time spent reading and commenting on manuscripts not only improves the manuscripts themselves but also increases the scientific rigor of future research in the field. Many of those listed below went above and beyond and reviewed three or more manuscripts for our journal, and those are indicated in italics. Together, they contributed 3674 individual reviews of manuscripts submitted to Water Resources Research for consideration, of which 562 were eventually published. Thank you again. We look forward to a 2017 of exciting advances in the field and communicating those advances to our community and to the broader public.